A micro‐computed tomography study of the negotiation and anatomical feature in apical root canal of mandibular molars. Issue 6 (14th June 2016) - Min, Yi; Ma, Jing‐Zhi; Shen, Ya; Cheung, Gary Shun‐Pan; Gao, Yuan
Summary: The aim of this study was to investigate the clinical negotiation of various apical anatomic features of the mandibular first molars in a Chinese population using micro‐computed tomography (micro‐CT). A total of 152 mandibular first molars were scanned with micro‐CT at 30 µm resolution. The apical 5 mm of root canal (ARC) was reconstructed three dimensionally and classified. Subsequently, the access cavity was prepared with the ARC anatomy blinded to the operator. The ARC was negotiated with a size 10 K file with or without precurve. Information on the ability to obtain a reproducible glide path was recorded. The anatomical classification of ARC was Type I with 68.45% in mandibular first molars. The negotiation result of ARC with Category i was 387 canals (74.00%). With a bent negotiating file, 96 canals were negotiated, including 88 reproducible glide paths (Category ii) and 8 irregular glide paths (Category iii). About 7.65% canals could not be negotiated with patency successfully (Category iv). The statistical analyze shown the anatomic feature of ARC had effect on the negotiation of ARC (p < 0.05). In conclusion, ARC anatomic variations had a strong potential impact on the negotiation. The category of negotiation in ARC would be helpful in the using of NiTi rotary instruments. Negotiation of ARC to the working length with patency should be careful and skillful because of the complexities of ARC. SCANNING 38:819–824, 2016. © 2016 Wiley Periodicals, Inc.